Building bricks with PCM inserts for Passive cooling applications. Issue 1 (October 2020) - Anfas Mukram, T; Daniel, Joseph
Abstract: The vital predicament that mankind will face in near future is the deficiency of energy. Heavy dependency of fossil fuels for driving the systems make the problem too complex by adding the Green House Gas (GHG) emission also. Across the sphere, consumption pattern confirms the major role of building sector, mostly for space conditioning application. Passive cooling by Latent Heat Thermal Energy Storage is well-established method. In this work commercially available Phase Change Material (PCM) is used for latent heat storage. The PCM is inserted in the brick cavity. The performance of two types of PCM insert is compared, ie, macro encapsulation at the middle of the brick and microencapsulation near the outer wall of the brick. The results show that, the centrally encapsulated brick performs better in heating cycle, but during night time the heat entry into the living space is more. The micro encapsulation at offset to the wall side justifies for the night use.